Les barrages qui cachent l’eau : l'oubli des vulnérabilités aux inondations lors de l’aménagement de la Dordogne (1917-1935) - Alexis Metzger; Jamie Linton (VertigO)
A series of large hydro-electrical dams was built on the Dordogne River over the course of the twentieth century. Given the historical prevalence of floods in the basin, it is striking to find virtually no mention of flood risk or vulnerability in the technical studies and documentation that preceded construction of dams between the two World Wars. Drawing from local archival research, this article attempts to understand why flood risk and vulnerability was forgotten, or ignored, in the development of these projects. It gives us some retrospective insight into vulnerabilities that are very much present today.